THE ROLE OF ANTICOAGULATION THERAPY IN PATIENTS WITH PROSTHETIC HEART VALVES - N. A. Shostak; A. A. Klimenko; D. Y. Andriyashkina; A. A. Kondrashov; A. V. Novikova (Klinicist)
Cardiac surgery is the only radical method of treatment of valvular defects (congenital or acquired): valve preservation procedures or prosthetics operations. 250 000 – 280 000 valve prostheses are implanted every year worldwide, while the number of prosthetic valves operation increases by an average of 5–7 % per year (biological prostheses – 8–11 %, mechanical prostheses – 3–5 %). Selection of biological or mechanical types of prosthesis, its location, the presence of associated risk factors for embolic events, such as atrial fibrillation, previous embolism, left ventricular dysfunction, hypercoagulable states determine patient management tactics. Particularly high risk of prosthetic thrombosis and thromboembolic complications can be seen in case of mechanical prosthesis implantation. Numerous prospective and retrospective clinical studies have proven high effectiveness of anticoagulants for reduction the risk of cardioembolic complications. The degree of anticoagulation (optimal international normalized ratio (INR)) is determined by risk factors for prosthetic thrombosis and thromboembolic complications in a patient, as well as thrombogenicity of the prosthesis by itself; INR may range from 2.5 to 4.0. International recommendations take into account the presence/absence of additional risk factors for thromboembolism, and based on warfarin administration with the achievement of target INR values combined with low-dose aspirin. Administration of novel direct oral anticoagulation remedies in patients with prosthetic heart valves has not been studied sufficiently up to date and is contraindicated. Thus, warfarin currently is a drug of choice for the prevention of thromboembolic complications in patients with prosthetic heart valves.